The Slow, Lingering Death of the English NHS; Comment on "Who Killed the English National Health Service?" - David J. Hunter (Kerman University of Medical Sciences, 2016)
The death of the English National Health Service (NHS) may be slow in coming but that does not mean that it is not the Conservative-led UK government's desired end state. The government is displaying tactical cunning in achieving its long-term purpose to remould the British state. Powell seeks greater clarity amidst the confusion but the lack of clarity is a principal weapon in the government's assault on the public realm, including the NHS. Moreover, there is ample supporting evidence to caution against Powell's tendency to complacency concerning the ultimate fate of the NHS.